BUILDING CHARACTERS OF PRIMARY SCHOOL STUDENTS THROUGH LAGU DOLANAN ANAK (KID’S PLAYING SONGS) BY USING THE ROLE-PLAYING METHOD - Heldisari, Hana Permata (Journal of Education Research and Evaluation, 2020)
Lagu dolanan anak as one form of culture that can be used as a means of conveying advice so that it is often assumed to be used as a means of character building in children. A form of preservation of lagu dolanan anak can be done through learning by using effective methods in achieving learning objectives. In this case, the purpose of learning lagu dolanan anak with the role-playing method was to understand the meaning of playing songs through learning activities of art and culture skills, with music art materials. Lagu dolanan anak studied wereAna Tamu, Cublak-Cublak Suweng, Dondhong Apa Salak, and Kuwi Apa Kuwi. The lyrics of those playing songs have been analyzed to have positive character values that are right taught to children. Through descriptive analytic from the facts, nature, the relationships between those lagu dolanan anak, role-playing learning method, and early characters building to studentswere described systematically, factually, and accurately. Learning lagu dolanan anak songs through the role-playing method contains nine-character values, namely independence, honesty, discipline, tolerance, hard work, creative, respect for achievement, and responsibility.